Literatur Review: Peran Guru dalam Mendukung Kesehatan Mental Siswa - Ainy Fardana, Nur; Iliyatunnisa, Iliyatunnisa (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2025)
Student mental health is an important aspect of education that significantly impacts their academic, social, and emotional development. Teachers play a role in supporting students' mental health. However, previous research has not specifically mentioned the role that teachers can play in supporting students' mental health. Therefore, this study aims to explore the role of teachers in supporting students' mental health using a Systematic Literature Review (SLR) approach. Data were collected from the Scopus and PubMed databases using specific keywords, with stages of time frame, data selection, article selection, and article classification carried out on the covidence application and resulting in 13 articles selected through the PRISMA protocol. The results of the study indicate that teachers have a central role in supporting students' mental health through six main strategies: (1) identifying mental health problems, (2) building positive relationships, (3) providing psychosocial support, (4) creating a conducive learning environment, (5) implementing intervention programs, and (6) collaborating with mental health professionals. These findings provide a clear conceptual framework of six teacher strategies in supporting students' mental health, as well as providing guidance for teachers on concrete actions that can be taken to support students' mental health.